2020
DOI: 10.1039/d0se00784f
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable energy and fuels from biomass: a review focusing on hydrothermal biomass processing

Abstract: Fossil fuels must be replaced with renewable energy resources to ensure sustainable development, reduce the dependence on fossil fuels, address environmental challenges including climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(97 citation statements)
references
References 198 publications
0
97
0
Order By: Relevance
“…† It can be concluded that the intrinsic reaction rates were measured in all experiments and that the reactor can be described by the balance equations of an ideal plug ow reactor. Furthermore, the volume contraction caused by reaction can be accounted for by eqn (6).…”
Section: Reactor Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…† It can be concluded that the intrinsic reaction rates were measured in all experiments and that the reactor can be described by the balance equations of an ideal plug ow reactor. Furthermore, the volume contraction caused by reaction can be accounted for by eqn (6).…”
Section: Reactor Modelmentioning
confidence: 99%
“…4,5 DME is produced from synthesis gas, which originates from different sources such as coal, natural gas, and waste materials like biomass. [4][5][6] Depending on the raw material and syngas production process, the composition of the syngas may change in a wide range, resulting in a variable feedstock for the DME synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The energy insecurity posed by the rapid depletion of fossil fuels and the environmental impact of using the fuels have motivated researchers to study biomass as an alternative fuel source for energy production. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, fossil fuels shortages have led industries to seek alternative strategies due to the nonrenewability of petroleum, metal mineral, coal and natural gas et al (Li et al 2020). The high energy demand in modern industry has led to an increase in the use of renewable energy, such as wind energy (Zhou et al 2012), tidal energy (Douziech, Hellweg, and Verones 2016), solar energy (Phan et al 2018), biomass energy (Lee et al 2010;Zhang et al 2019) and geothermal energy (Alper et al 2020), because they are not restricted by distribution and content of fossil fuels, without exhaust gases and environmentally friendly procedure. However, these energies have the disadvantages of high operation cost, low e ciency, and large uctuations by climate and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%